md-Matrix: An assistive learning tool in blended project-based learning for mobile development course - Sarif, Siti Mahfuzah; Shiratuddin, Norshuhada (The University of Auckland, Auckland University of Technology, and Australasian Society for Computers in Learning in Tertiary Education (ascilite), 2009)
This study reports on the use of project based learning (PBL) in a blended environment as key method for teaching practical mobile application development within the context of undergraduate program module in mobile programming course in Universiti Utara Malaysia. In support of the use of PBL, a prototype known as md-Matrix has been used throughout this study and will be proposed as the learning tool for mobile development course. The tool is designed and developed to assist students in choosing an appropriate development methodology based on their project requirements. Descriptions of how md-Matrix can be used in facilitating the learning process are described in this paper.